1974
DOI: 10.1111/j.1432-1033.1974.tb03792.x
|View full text |Cite
|
Sign up to set email alerts
|

Two Specific Ribonucleoprotein Fragments from the 50-S Sub-Particle of Escherichia coli Ribosomes

Abstract: 50-S ribosomal particles from Escherichia coli were hydrolysed with ribonuclease TI, and the ribonucleoprotein fragments produced were fractionated on polyacrylamide gel. The proteins contained in these fragments were analysed on gels containing the detergent sarkosyl (N-laurylsarcosine), using the technique already published. Two-dimensional gel electrophoresis was used for the final identification of the proteins.Two very specific fragments were obtained, the smaller containing only proteins L1 and L9, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

1975
1975
1993
1993

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…(The strong spot to the left of spot 59 is the 32P-ink used to mark the fingerprint.) print closely resembles that of the total RNA from the small ribonucleoprotein fragment "Band III" (13) , and examples of some unambiguous characteristic oligonucleotides, whose identities were confirmed where necessary by secondary digestion with ribonuclease A (see Materials and Methods) are :-spot 59 and/or 47 (sections 0' and D respectively), spot 3-11 (section 0'), spot [6][7][8][9][10][11][12][13][14][15][16] (section K), spots 38a and 29a (section P), spot 2-llb (section E) and spots 16i and 26a (section A) (see Fig. 5).…”
Section: Amentioning
confidence: 85%
See 1 more Smart Citation
“…(The strong spot to the left of spot 59 is the 32P-ink used to mark the fingerprint.) print closely resembles that of the total RNA from the small ribonucleoprotein fragment "Band III" (13) , and examples of some unambiguous characteristic oligonucleotides, whose identities were confirmed where necessary by secondary digestion with ribonuclease A (see Materials and Methods) are :-spot 59 and/or 47 (sections 0' and D respectively), spot 3-11 (section 0'), spot [6][7][8][9][10][11][12][13][14][15][16] (section K), spots 38a and 29a (section P), spot 2-llb (section E) and spots 16i and 26a (section A) (see Fig. 5).…”
Section: Amentioning
confidence: 85%
“…Each 20 41 aliquot was treated with 2 41 of ribonuclease A (0.1 4g/ml) for 1 hr at 25°C, and enzyme was removed by applying the solution to a 3% polyacrylamide-agarose gel containing 1 mM magnesium and 20 mM potassium, at pH 7.8 (14). The gel was run until a bromophenol blue marker had travelled 10 cm, and was then sliced and analysed for radioactivity.…”
Section: Preparation Of Ribosomal Subunitsmentioning
confidence: 99%
“…2) and applied to two-dimensional gels, exactly as described (2,16). In other experiments, 50S subunits were dialysed against 10 mM Tris-HCl pH 7.8, 0.03 mM magnesium acetate, treated with ribonuclease T1 (12-50 units enzyme per A260 unit 50S) as described previously (17), and applied to a 5-20% polyacrylamide gradient gel containing 5 mM magnesium at pH 6 (cf. 18): This treatment releases a large number of free RNA fragments from the subunit, and regions of the gel containing these fragments (cf.…”
Section: Methodsmentioning
confidence: 99%
“…Cross-linking experiments have demonstrated that the L9 protein is located in the vicinity of proteins L2 [6, 10], L10 [3] and L28 [24] in the ribosome. It is likely that this protein is also associated with proteins L1 [ 15,18], L3, L18 and L23 since these proteins are found in a small ribonucleoprotein fragment obtained from the 50S ribosomal subunit by controlled nucleolytic digestion [ 18 ].Only a few of the proteins in cyanobacterial ribosomes have been characterized. Genes for the 30S ribosomal proteins $2 $7 and S 12, namely, rps2, rps7 and rpsl2, respectively, have been cloned from Spirulinaplatensis [2,19], and the latter two have also been cloned from Anacystis nidulans [13].…”
mentioning
confidence: 99%
“…Cross-linking experiments have demonstrated that the L9 protein is located in the vicinity of proteins L2 [6,10], L10 [3] and L28 [24] in the ribosome. It is likely that this protein is also associated with proteins L1 [ 15,18], L3, L18 and L23 since these proteins are found in a small ribonucleoprotein fragment obtained from the 50S ribosomal subunit by controlled nucleolytic digestion [ 18 ].…”
mentioning
confidence: 99%